A poly(neutral red)/porous graphene modified electrode for a voltammetric hydroquinone sensor. (1st December 2022) - Chuenjitt, Sariktiya; Kongsuwan, Ananya; Phua, Cheng Ho; Saichanapan, Jenjira; Soleh, Asamee; Saisahas, Kasrin; Samoson, Kritsada; Wangchuk, Sangay; Promsuwan, Kiattisak; Limbut, Warakorn
Highlights: Poly(neutral red) film was formed on a porous graphene modified electrode. The modified electrode was applied to determine hydroquinone. The electrochemical sensor was sensitive, fast, simple and accurate. Hydroquinone was reliably determined in skin whitening creams. Abstract: In this work, a glassy carbon electrode was modified with poly(neutral red)/porous graphene (PNR/P-Gr/GCE). The electrode was developed for use in an electrochemical sensor to determine hydroquinone (HQ) in skin whitening creams. The electrode was prepared by drop casting P-Gr on the GCE surface, followed by electro-polymerization of neutral red in deep eutectic solvent (DES) without an acid dopant. The fabrication of the electrode was optimized and then characterized by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). The electrochemical properties of the electrode were investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The PNR/P-Gr/GCE was used to determine HQ by adsorptive stripping differential pulse voltammetry (AdSDPV). Under optimal detection conditions, the electrode was 2 and 5 times more sensitive toward HQ than a P-Gr/GCE and an unmodified electrode, respectively. The developed electrode determined HQ concentrations from 0.005 to 70 µg mL −1 and exhibited a detection limit of 1.7 ng mL −1 . The preparation of the electrode showed good repeatability (RSDs between 2.19 and 3.83%, n = 15), reproducibility (RSD < 1.87%, n = 6), and anti-interference properties. The proposed method successfully quantified HQ in skin whitening creams with recoveries between 89 ± 2 and 105.1 ± 0.2%. There was no significant difference at a 95% confidence level between the results obtained using the proposed method and those from UV-derivative spectrophotometry. This electrode presents a promising approach to HQ determination in skin whitening creams. Graphical abstract: Image, graphical abstract